Correlation between carcinoembryonic antigen, cancer antigen 15-3, and neutrophil–lymphocyte ratio on metastasis and progression-free survival of breast cancer - Rianse, Muhammad Alim Al Fath; Syamsu, Salman Ardi; Jr , John Pieter; Prihantono , Prihantono; Hamid, Firdaus; Masadah, Rina; Faruk, Muhammad (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: Blood and tumor markers have been studied as predictive and prognostic factors in breast cancer (BC). To assess the relationships of the tumor markers cancer antigen 15-3 (CA 15-3) and carcinoembryonic antigen (CEA) and the neutrophil–lymphocyte ratio (NLR) with the incidence of metastasis and progression-free survival (PFS) in BC. Methods: This observational analytical study used a cohort design. The population was BC patients who had undergone mastectomy or breast-conserving treatment. Patients received CEA and CA 15-3 examinations and were assessed radiologically for metastases, with follow-up of up to 24 months. Differences in patient PFS levels depending on NLR, CEA, and CA 15-3 were assessed using Kaplan–Meier analysis. Results: One male and 159 female patients were included, with a mean age of 48.3 ± 9.18 years. The mean NLR, CEA, and CA 15-3 were 22.51 ± 94.1, 73.05 ± 212.99, and 2.56 ± 3.48, respectively. Based on a mean PFS of 12.16 ± 0.45, 38.4% of patients experienced metastases. A significant relationship with the incidence of metastasis existed for CA 15-3 and CEA levels but not NLR. Likewise, PFS did not show a significant relationship with NLR, CA 15-3, or CEA. Survival analysis showed no significant relationship. Conclusions: CEA and CA 15-3 can be negative prognostic factors for BC metastasis. These results can be compared with other studies, specifically answering the role of predictive and prognostic factors of NLR, CEA, and CA 15-3 in BC patients.